Penerapan Metode Naïve Bayes Untuk Menentukan Penilaian Kinerja Karyawan PT.Sinergi Guna Solusindo - Ajat Sudrajat (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Determining performance appraisal is an important thing to be carried out by companies where career development efforts for a contract employee have been carried out during the contract agreement period. Good and quality employees of course have a positive impact on the companies where they work. The criteria used to determine whether an employee is worthy or not to become a permanent employee are attendance, personality, achievement, and so on. One method that can be used for this is the data mining method or the Naive Bayes algorithm method. The Naive Bayes Classifier algorithm is one of the statistical classifiers, where this classifier can predict the probability of class membership of a data that will fall into a certain class, according to the probability calculation. This analysis uses rapidminer which is a data analysis software with features of several algorithms that are easy to operate. Prediction results using rapidminer to determine employee performance quickly and accurately, from tests conducted by comparing field data with testing data obtained an accuracy rate of 94%.